The dynamic evolution of swelling in nickel concentrated solid solution alloys through in situ property monitoring. (December 2021) - Dennett, Cody A.; Dacus, Benjamin R.; Barr, Christopher M.; Clark, Trevor; Bei, Hongbin; Zhang, Yanwen; Short, Michael P.; Hattar, Khalid
Highlights: Non-contact laser metrology used to track the dynamic thermoelastic properties of nickel concentrated solid solution alloys during ion beam irradiation. Direct property measurement captures features from accumulated defects of all length scales. Irradiation-induced void swelling is monitored through changes in local elasticity. Graphical abstract: Abstract: Defects and microstructural features spanning the atomic level to the microscale play deterministic roles in the expressed properties of materials. Yet studies of material evolution in response to environmental stimuli most often correlate resulting performance with one dominant microstructural feature only. Here, the dynamic evolution of swelling in a series of Ni-based concentrated solid solution alloys under high-temperature irradiation exposure is observed using continuous, in situ measurements of thermoelastic properties in bulk specimens. Unlike traditional evaluation techniques which account only for volumetric porosity identified using electron microscopy, direct property evaluation provides an integrated response across all defect length scales. In particular, the evolution in elastic properties during swelling is found to depend significantly on the entire size spectrum of defects, from the nano- to meso-scales, some of which are not resolvable in imaging. Observed changes in thermal transport properties depend sensitively on the partitioning of electronic and lattice thermal conductivity. This emerging class of in situ experiments, which directly measure integrated performance in relevant conditions, provides unique insight into material dynamics otherwise unavailable using traditional methods.